Limonin, an AMPK Activator, Inhibits Hepatic Lipid Accumulation in High Fat Diet Fed Mice - Si-wei Wang; Tian Lan; Hang-fei Chen; Hao Sheng; Chun-yi Xu; Li-feng Xu; Fang Zheng; Feng Zhang (Frontiers Media S.A., 2022)
NAFLD is the most prevalent liver disease in human history. The treatment is still limited yet. In the current study, we reported that limonin inhibited hepatic lipid accumulation and fatty acid synthesis in HFD fed mice. Using AMPK inhibitor and AMPK deficient C. elegans, we revealed the effect was dependent on the activation of AMPK. We found that limonin activated AMPK through inhibition of cellular energy metabolism and increasing ADP:ATP ratio. Furthermore, the treatment of limonin induced AMPK mediated suppression of the transcriptional activity of SREBP1/2. Our study suggests that limonin may a promising therapeutic agent for the treatment of NAFLD.